مسالك الإمام البوني في التفسير من خلال كتابه " تفسير الموطأ" - غمام نواس, نور الهدى (University of Eloued جامعة الوادي, 2018)
"يتضمن البحث دراسة لمسالك الإمام أبي عبد الملك البوني في التفسير من خلال كتابه الذي شرح فيه موطأ الإمام مالك، والمعنون بـ:"" تفسير الموطأ""، حيث قسمت مضمون الدراسة إلى ثلاثة مباحث، الأول تناولت فيه التعريف بالمؤلف، والثاني تناولت فيه التعريف بالكتاب، وضمنت المبحث الثالث الدراسة التطبيقية للموضوع، والتي تمثلت في بيان جهود الإمام البوني في التفسير، ومسالكه في ذلك، وقد خلصت إلى عدة نتائج أهمها: * أن البونيرحمه الله استفاد من مصادر التفسير(القرآن والسنة، وآثار الصحابة، وآثار السلف، واللغة العربية) في بيان القرآن. * أنه لم يضع منهجا معينا يفسّر على أساسه بل يذكر من الآية ما يناسب المقال أثناء شرحه للحديث. * أنّه له جهد نفيس في بيان النص القرآني يتطلب مزيد من العناية لإبرازه والاستفادة منه. وصلّ اللهم على سيدنا محمد وعلى آله وصحبه أجمعين." "The research includes a study of the efforts of Imam Abi Abd al-Malik al-Boni in the interpretation through his book, which explained the mawta of Imam Malik, entitled: ""Tafsir al-Mawatta"" The third topic covered the practical study of the subject, which was a statement of the efforts of Imam Al-Boni in the interpretation, and its path in that, and has concluded several results, the most important of which are: * Bony - may God have mercy on him - benefited from the sources of interpretation (Quran and Sunnah, and the effects of companions, and the effects of the advances, and Arabic) in the statement of the Koran. * He did not develop a specific methodology is explained on the basis of it but mentions from the verse what fits the article during his explanation of the talk. * It is a valuable effort in the statement of the Koran requires more attention to highlight and benefit from it. God prayed on prophet Mohamed and his whole family and companions. "
مذكرة ماستر تخصص تفسير وعلوم القرآن
Keywords: مسالك - الإمام – البوني - خلال كتابه - "تفسير الموط; Pathways - Imam - Albony - during his book - "interpretation of the dead"